DUKUNGAN ORANG TUA DAPAT MENINGKATKAN PRESTASI SISWA BOARDING SCHOOL DI MI MAMBAUL ULUM POWAK TLONTO RAJA PASEAN PAMEKASAN - Endang Fauziyah Susilawati; Abdan Syakura; Dinar Vincy Y.B (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
There are many parents who still didn’t know about the development of school model for children with elementary school levels. This condition clarified by the lack of socialization from government relate with the role of model in elementary. Research design that is use in this research is correlative cross sectional analytical study. Analytical design is research design that testing the correlation between variables which aims to find a relationship of parental support and students achievement. The result of both variables tested by SPSS Rank Spearman. The population in this research is student’s family of MI Mambaul Ulum from 4-6 grade as many as 34 people. The result showed that sig 2 tailed is 0,001 < 0,05 so the hypothesis is accepted. It means that there is a correlation between parental support with students achievement at Mambaul Ulum boarding school Tlonto Raja Pasean sub-district, Pamekasan regency. The improving of children’s achievement can increase prosperity in future, children are the next generation who will carry out the interests of nation especially for their area where their live. Keywords : Achievement, children, boarding school